Yuttitham chumchon Trang : krabūankān sāng khrư̄akhāi yuttitham chumchon sū sangkhom pen suk (Samnakngān Kō̜ngthun Sanapsanun Kānwičhai (Sō̜kō̜wō̜.) Fāi Wičhai phư̄a Thō̜ngthin, 2009)
On community networking in Trang Province, Southern Thailand, for social justice and peace.